The role of sleep state and time of day in modulating breathing in epilepsy: implications for sudden unexpected death in epilepsy - Joyal, Katelyn G.; Kreitlow, Benjamin L.; Buchanan, Gordon F. (Frontiers in Neural Circuits, 2022)
Sudden unexpected death in epilepsy (SUDEP) is the leading cause of death among patients with refractory epilepsy. While the exact etiology of SUDEP is unknown, mounting evidence implicates respiratory dysfunction as a precipitating factor in cases of seizure-induced death. Dysregulation of breathing can occur in epilepsy patients during and after seizures as well as interictally, with many epilepsy patients exhibiting sleep-disordered breathing (SDB), such as obstructive sleep apnea. The majority of SUDEP cases occur during the night, with the victim found prone in or near a bed. As breathing is modulated in both a time of day and sleep state-dependent manner, it is relevant to examine the added burden of nocturnal seizures on respiratory function. This review explores the current state of understanding of the relationship between respiratory function, sleep state and time of day, and epilepsy. We highlight sleep as a particularly vulnerable period for individuals with epilepsy and press that this topic warrants further investigation in order to develop therapeutic interventions to mitigate the risk of SUDEP.